Use of Remote Ischemic Preconditioning in Cardiosurgical Patients - V. V. Lomivorotov (Obŝaâ Reanimatologiâ, 2011)
Objective: to study the cardioprotective effect of remote ischemic preconditioning (RIP) in cardiosurgical patients operated on under extracorporeal circulation (EC). Subjects and methods. Fifty-two patients with coronary heart disease (mean left ventricular ejection fraction 58.9±7.4%) operated on under EC and inhaled isofluorane anesthesia were examined. All the patients were randomized into two groups: 1) RIP; 2) without RIP. Central hemodynamic parameters and the plasma levels of troponin I, creatinine phosphokinase (CPK), and CPK-MB were estimated in the intraoperative and early postoperative period. Results. Before EC, cardiac index was significantly higher in the study group than that in the control one [2.31 (1.99; 2.5) and 2.05 (1.91; 2.25) bmin/m2, respectively; p<0.05]. Before EC, there was a significant increase in stroke index in the study group as compared with the control one [41.4 (34.73; 51.25) and 36 (28.87; 41.28) ml/m2, respectively; p<0.05]. In the study group, the significant excess was retained immediately after EC [40.89 (36.53; 42.15) and 35.14 (32.2; 37.24) ml/m2, respectively; p<0.05]. There were no statistically significant intergroup differences in the concentration of serum markers of injury. Conclusion. A positive hemodynamic effect is observed when a procedure for RIP is used in patients with coronary heart disease during direct myocardial revascularization under EC at the preperfusion stage. Key words: remote ischemic preconditioning, troponin I, extracorpo-real circulation, myocardial protection.